2019
DOI: 10.31557/apjcp.2019.20.10.2897
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Haptoglobin Genotype and Some Risk Factors of Cancer in Patients with Early Stage Esophageal Cancer

Abstract: Introduction: Esophageal cancer is one of the most lethal gastrointestinal cancers that has a complex and diverse etiology, with several genetic and nutritional factors involved in its etiology. The purpose of this study was to investigate the type of haptoglobin genotype and its relationship with some nutritional and biochemical risk factors affecting the prevalence of esophageal cancer in patients with early stage esophageal cancer. Materials and methods: In this study, 44 patients (20 males and 24 females) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It is the eighth most common cancer and the sixth most common cause of cancer death globally [ 2 ]. In Iran, esophageal cancer is more popular than any other countries or regions in the world [ 3 ]. Classified by histology, esophageal cancer is divisible into adenocarcinoma and squamous cell carcinoma (ESCC) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is the eighth most common cancer and the sixth most common cause of cancer death globally [ 2 ]. In Iran, esophageal cancer is more popular than any other countries or regions in the world [ 3 ]. Classified by histology, esophageal cancer is divisible into adenocarcinoma and squamous cell carcinoma (ESCC) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Men with WC > 102 cm and women with WC > 88 cm are at higher risk of obesity disorders than those below these thresholds [ 42 44 ]. Bodyweight and height were measured using a Seca scale with an accuracy of 100 gr and a Seca stadiometer with an accuracy of 0.5 cm, respectively; subsequently, BMI, as general obesity index, was computed as the body weight (kg) divided by the square of height (m) [ 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is not only a sign of a well-balanced diet but also negatively correlated with many diseases. A study has shown that lower consumption of fresh vegetables and fruits is a risk factor for ESCA, while modifying the nutritional model can effectively reduce the prevalence of ESCA 41 . Scientists from the National Cancer Institute and the Cancer Institute of the Chinese Academy of Medical Sciences jointly launched a nutritional intervention experiment in the Taihang Mountain areas to reduce the incidence and mortality of ESCA.…”
Section: Risk Factors For Escamentioning
confidence: 99%
“…It is not only a sign of a well-balanced diet but also negatively correlated with many diseases. A study has shown that lower consumption of fresh vegetables and fruits is a risk factor for ESCA, while modifying the nutritional model can effectively reduce the prevalence of ESCA 41 Beneficial effects can still be observed 10 years after stopping the supplement 42 . The above illustrated the importance of vitamin supplementation for the occurrence and development of ESCA and provided ideas for the prevention and treatment of ESCA.…”
Section: Dietary Factors With High Incidence Of Esca In the Taihang M...mentioning
confidence: 99%